2007
DOI: 10.1007/s00253-007-1009-6
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological intensification of biogas production

Abstract: The importance of syntrophic relationships among microorganisms participating in biogas formation has been emphasized, and the regulatory role of in situ hydrogen production has been recognized. It was assumed that the availability of hydrogen may be a limiting factor for hydrogenotrophic methanogens. This hypothesis was tested under laboratory and field conditions by adding a mesophilic (Enterobacter cloacae) or thermophilic hydrogen-producing (Caldicellulosyruptor saccharolyticus) strain to natural biogas-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(80 citation statements)
references
References 31 publications
2
72
0
6
Order By: Relevance
“…The maximum level of biogas production in R4 was possibly due to acidogenis and methanogenisis, indicating a promising role of mixed bacterial cultures. It has been previously reported that the addition of active inoculum containing mixed bacterial cultures in the bioreactor proved to be more promising for biogas production at 35ºC and 55ºC [26].…”
Section: Biogas Production In Four Different Reactorsmentioning
confidence: 99%
“…The maximum level of biogas production in R4 was possibly due to acidogenis and methanogenisis, indicating a promising role of mixed bacterial cultures. It has been previously reported that the addition of active inoculum containing mixed bacterial cultures in the bioreactor proved to be more promising for biogas production at 35ºC and 55ºC [26].…”
Section: Biogas Production In Four Different Reactorsmentioning
confidence: 99%
“…The maintenance of an extremely low pressure of hydrogen is essential for the acetogenic and hydrogen producing bacteria. Although many microbial details of metabolic networks in a methanogenic consortium are not clear, present knowledge suggests that hydrogen may be a limiting substrate for methanogens [2]. This assumption is based on the fact that addition of hydrogen producing bacteria to the natural biogas-producing consortium increases the daily biogas production.…”
Section: Introductionmentioning
confidence: 99%
“…In the long term, there is great interest in the engineering of microorganisms that can produce hydrogen directly from anaerobic digestion of biomass. 20,21 This effort is still early in the research phase, but it shows great promise as an inexpensive source of hydrogen if successful. Another novel concept is an integrated biofuel-feedlot facility where animal feed is a coproduct of biofuel production and AD is used to augment power generation.…”
Section: Anaerobic Digestionmentioning
confidence: 99%